Activity and Coupling to Hippocampal Oscillations of Median Raphe GABAergic Cells in Awake Mice - Jelitai, Marta; Barth, Albert M.; Komlósi, Ferenc; Freund, Tamás F.; Varga, Viktor (Frontiers in Neural Circuits, 2021)
Ascending serotonergic / glutamatergic projection from the median raphe region (MRR) to the hippocampal formation regulates both encoding and consolidation of memory and the oscillations associated with them. The firing of various types of MRR neurons exhibit rhythmic modulation coupled to hippocampal oscillatory activity. A possible intermediary between rhythm-generating forebrain regions and entrained ascending modulation may be the GABAergic circuit in the MRR known to be targeted by a diverse array of top-down inputs. However, activity of inhibitory MRR neurons in the awake animal is still largely unexplored. In this study, we utilized whole cell patch-clamp, single cell and multichannel extracellular recordings of GABAergic and non-GABAergic MRR neurons in awake, head-fixed mice. First, we have demonstrated that glutamatergic and serotonergic neurons receive both transient, phasic and sustained tonic inhibition. Then, we observed substantial heterogeneity of GABAergic firing patterns but a marked modulation of activity by brain states and fine timescale coupling of spiking to theta and ripple oscillations. We also uncovered a correlation between preferred theta phase and direction of activity change during ripples suggesting the segregation of inhibitory neurons into functional groups. Finally, we could detect complementary alteration of non-GABAergic neurons’ ripples-coupled activity. Our findings support the assumption that the local inhibitory circuit in the MRR may synchronize ascending serotonergic / glutamatergic modulation with hippocampal activity on a subsecond timescale.